2021
DOI: 10.1039/d1ra00013f
|View full text |Cite|
|
Sign up to set email alerts
|

The effect of pH and transition metal ions on cysteine-assisted gold aggregation for a distinct colorimetric response

Abstract: Divalent transition metal ions facilitated the aggregation of gold nanoparticles: Fe2+ < Ni2+ < Zn2+ < Co2+ ≪ Mn2+ < Cu2+ at pH 7. The optimized AuNPs-Cu2+ system produced the progressive color change upon the addition of cysteine (0.2–2.0 μM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 52 publications
0
11
0
Order By: Relevance
“…High salt levels can neutralize the stabilizing electrostatic forces on AuNPs, causing the van der Waals forces to drive the conversion of dispersion into aggregation [ 58 ]. Another strategy involves the ion-induced aggregation of AuNPs [ 51 , 55 , 59 ]. For example, Mn 2+ can interact with carboxyl groups on the AuNP surface and lead to the aggregation of AuNPs, resulting in a change in color from red to purple.…”
Section: Colorimetric Detection and Monitoring Strategies Of Bacteria...mentioning
confidence: 99%
See 1 more Smart Citation
“…High salt levels can neutralize the stabilizing electrostatic forces on AuNPs, causing the van der Waals forces to drive the conversion of dispersion into aggregation [ 58 ]. Another strategy involves the ion-induced aggregation of AuNPs [ 51 , 55 , 59 ]. For example, Mn 2+ can interact with carboxyl groups on the AuNP surface and lead to the aggregation of AuNPs, resulting in a change in color from red to purple.…”
Section: Colorimetric Detection and Monitoring Strategies Of Bacteria...mentioning
confidence: 99%
“…For example, Mn 2+ can interact with carboxyl groups on the AuNP surface and lead to the aggregation of AuNPs, resulting in a change in color from red to purple. A recent study reported that the addition of Mn 2+ and Cu 2+ facilitates the cysteine-induced aggregation of AuNPs [ 59 ]. The thiol group of cysteine strongly binds to the AuNP surface, forming a zwitterionic structure with carboxyl and ammonium groups [ 60 ].…”
Section: Colorimetric Detection and Monitoring Strategies Of Bacteria...mentioning
confidence: 99%
“…In the field of biosensing, noble (Au and Ag) metallic nanoparticles (NMNPs) with their unique optical properties are of great interest given their importance in the development of colorimetric and surface plasmonic resonance (SPR) biosensors, as well as surface-enhanced Raman scattering (SERS)active materials. [8][9][10][11][12][13] Gold NPs (Au NPs) possess attractive features such as chemical stability and ease of surface modification, which are imperative for sensing applications. 10,[14][15][16][17][18][19] The plasmonic efficiency of silver nanoparticles (Ag NPs) is higher than that of Au NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Gold NPs (Au NPs) possess attractive features such as chemical stability and ease of surface modification, which are imperative for sensing applications. 10,[14][15][16][17][18][19] The plasmonic efficiency of silver nanoparticles (Ag NPs) is higher than that of Au NPs. [20][21][22] In addition, some studies have shown that Ag NPs can be used as colorimetric sensors for dopamine detection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation